Problems of High School Students Based on Alat Ungkap Masalah Umum - Rahmi, Annisa; Syukur, Yarmis (Current Issues in Counseling, 2023)
The background for writing this article is that there are students who do not know the problems they are experiencing, at school students are said to have problems, namely students who commit violations, there are students who do not want to be open to guidance and counseling teachers and instruments to reveal common problems have not been fully implemented. The provision of effective services should be based on accurate data tailored to the needs of students, therefore it is very necessary to administer the problem solving tool to students by the guidance and counseling teacher. This study aims to describe the problems experienced by students, describe problems that are considered difficult by students and describe parties to consult student problems. This research uses a descriptive quantitative approach. The population in this study were 639 students of SMAN 1 Lembah Gumanti, the sample was taken using a proportional random sampling technique, the number of samples was 247 students. The data collection technique uses the alat ungkap masalah umum in the SMA format-3. Data analysis techniques using descriptive statistical techniques. The results of this study indicate that the most common problems students experience are related to careers and jobs. Students do not know their own talents for what positions and jobs. Problems that are considered severe are related to physical and health, students feel the body is too thin or too fat. Furthermore, students want to consult the problem with guidance and counseling teachers, family, peers, and students do not want to consult the problem.